Congenital Muscular Dystrophy / Rigid Spine Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
A detailed phenotypic description of 4 siblings (3 boys and 1 girl) with congenital muscular dystrophy and rigid spine syndrome is reported from the University of Utah, Salt Lake City, UT.